Pendekatan Kuantitatif Dalam Studi Tata Letak Fasilitas Produksi - Pawitan, Gandhi; Desita, Donna (Jurnal Administrasi Bisnis, 2008)
One of the efforts to ensure the companyâs survival is to increase the efficiency of line balancing in company. The goals of this research are to get a scenario of how the line balancing in the company is done, observe the using of the line balancing method in order to increase the efficiency. This research used study case and descriptive analysis. The data collection was done by direct observation and interview with production division. The research was done at a manufacturing company that produces tapioca flour. The result showed that the line balancing in company is 39.21%, it means that the effective time the company used in line production is 39.21%. The efficiency of line balancing has not been reached yet because of the total operation time in every workstation has not balanced yet with cycle time, 0.0427 minutes. If the company apply the line balancing method, it could increase the efficiency up to 98.01%. The influencing factors of the line balancing are : the irregular supply of raw materials which eventually accumulated at certain time and thus, causing the machines to have an idle time. Keywords: Line balancing analysis, facility layout, efficiency, idle time